A Strongly Luminescent Chromium(III) Complex Acid. Issue 48 (10th August 2018) - Otto, Sven; Förster, Christoph; Wang, Cui; Resch‐Genger, Ute; Heinze, Katja
Abstract: The synthesis, structure, reactivity, and photophysical properties of a novel acidic, luminescent chromium(III) complex [Cr(H2 tpda)2 ] 3+ (2 3+ ) bearing the tridentate H2 tpda (2, 6‐bis(2‐pyridylamino)pyridine) ligand are presented. Excitation of2 3+ at 442 nm results in strong, long‐lived NIR luminescence at 782 nm in water and in acetonitrile. X‐ray diffraction analysis and IR spectroscopy reveal hydrogen‐bonding interactions of the counter ions to the NH groups of2 3+ in the solid state. Deprotonation of the NH groups of2 3+ by using a non‐nucleophilic Schwesinger base in CH3 CN switches off the luminescence. Re‐protonation by using HClO4 restores the emission. In water, the p K a value of2 3+ amounts to 8.8, yet deprotonation is not reversible in the presence of hydroxide ions. Dioxygen quenches the emission of2 3+, but to a weaker extent than expected. This is possibly due to the strong ion‐pairing properties of2 3+ even in solution, reducing the energy transfer efficiency to O2 . Deuteration of the NH groups of2 3+ approximately doubles the quantum yield and lifetime in water, demonstrating the importance of multiphoton relaxation in these NIR emitters. Abstract : Luminescent chromium complex : The NIR emissive complex [Cr(H2 tpda)2 ] 3+ (H2 tpda=2, 6‐bis(2‐pyridylamino)pyridine) is more acidic than [NH4 ] + and its NH protons easily exchange with deuterium in D2 O/DClO4 . This measure strongly enhances its luminescence quantum yield and emission lifetime. As the conjugate base [Cr(Htpda)(H2 tpda)] 2+ is non‐luminescent, the conjugate acid/base pair acts as a pH dependent luminescent on/off switch.